PENGARUH PEMBELAJARAN PENDIDIKAN PANCASILA TERHADAP KARAKTER BHINNEKA TUNGGAL IKA PESERTA DIDIK KELAS VII SMP NEGERI 1 KOTO GASIB - Stevani Prisillia; Sri Erlinda; Indra Primahardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted because it was motivated by the low character of Bhinneka Tunggal Ika of students, seen from the phenomenon faced by students where the lack of understanding of students towards diversity, where there is still a lack of being fair to everyone, there is still discrimination against friends, this happens to seventh grade students at SMP Negeri 1 Koto Gasib. This study aims to determine the effect of Pancasila Education learning on the character of Bhinneka Tunggal Ika of seventh grade students at SMP Negeri 1 Koto Gasib. The benefits of this research are that it can be a source of reference in education, can support teachers in developing their skills in managing classes, creating a positive learning environment, and guiding students in developing the character of Bhinneka Tunggal Ika. and this research can make it easier for students to understand the importance of unity in everyday life. This research method is descriptive quantitative, the data collection instruments used in this study are questionnaires, interviews and documentation. The population in this study were 123 seventh grade students at SMP Negeri 1 Koto Gasib. The sampling of this study was based on Sugiyono's theory which used the Simple Random Sampling technique using the Slovin formula with a precision of 10% so that the number of samples in this study was 50 students. The results of this study indicate that there is a positive and significant influence between Pancasila Education learning on the Bhinneka Tunggal Ika character of seventh grade students of SMP Negeri 1 Koto Gasib.